Penerapan Teknologi Sistem Hidroponik dan Perikanan Energi Baru Terbarukan Berbasis IoT untuk Mewujudkan Kemandirian Pangan dan Energi di Kelompok Tani Lestari Farm Sragen - Raden Danang Aryo Putro Satriyono; Rizki Nurilyas Ahmad; Titik Suryani (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Food security and energy independence are key pillars of sustainable village development toward the Golden Indonesia 2045 vision. The "Lestari Farm" Farmers Group in Karanganyar Village, Plupuh, Sragen, faces structural constraints in expanding its integrated hydroponic and catfish aquaculture operations. Major challenges include high electricity costs for circulation pumps (accounting for 30%–35% of total operational expenses), commodity mortality risks caused by power outages, uncontrolled water quality (yielding predominantly Grade B/C products), and manual, unsegregated financial management. This partnership program aims to implement "SI-HEBAT" (Sistem Hidroponik & Perikanan Energi Baru Terbarukan / Renewable Energy Hydroponic & Fishery System) technology, which integrates a 300 Wp off-grid solar power system with an Internet of Things (IoT) ESP32-based automated nutrient control system. The methodology employed is Participatory Action Research (PAR), encompassing stages of community engagement, technology fabrication, technical training, digital management mentoring, and the establishment of a sustainability unit. The results demonstrate 100% efficiency in operational electricity costs, a reduction in crop/fish mortality rates to less than 5%, and a quality upgrade to predominantly uniform Grade A harvests. Furthermore, the partner successfully adopted digital financial bookkeeping via an app and launched rebranded, labeled product packaging.